(untitled) (MAUSAM, 2017)
Solar radiation is the main source of energy for many physical, chemical and biological process .Estimation of solar radiation from other measured meteorological variables offers an important alternative in the absence of availability of measured solar radiation data. In this paper, we validate and assess five commonly used air temperature based models. The weather data of Dumdum (a station in Gangetic West Bengal) has been taken to observe whether the same works for this region or not. We have also validated and assessed a Local power-2 model (polynomial with degree two) with the same station, i.e., Dumdum (22.39° N, 88.27° E) and found it to give a more good result than Local model (linear in nature) so far developed. However the two step method to estimate solar radiation from the commonly measured air temperature in two steps gives more accurate estimation of solar radiation of a place. The model performance is evaluated using different law of error. Results show that the two step method gives good performance and significantly outperforms the temperature based models as claimed by our predecessors. The parameters of S/S0 equation were calculated by multiple regression model and was used `in the two step method for calculating the solar radiation. It is found that the two step method using the parameters determined by the proposed equations gives good performance. Therefore the two step method with the parameters determined by the proposed equations could also be used to estimate solar radiation in West Bengal and also at different places in India having similar topography. It is believed to be useful for the site where no measured solar radiation and sunshine duration data is available, whereas the air temperature are commonly measured.